Strategy for Management and Monitoring of Groundwater Quality in Oilcontaminated Soil Recovery Areas in Siak Regency, Riau Province - Setiawan, Khairi; Amin, Bintal; Wawan, Wawan (Jurnal Indonesia Sosial Sains, 2026)
Groundwater is an essential natural resource that supports ecological balance and human life; however, it is highly vulnerable to contamination from industrial activities, particularly oil and gas operations. Oil spills can cause significant environmental degradation, affecting soil quality, groundwater systems, and the socio-economic conditions of surrounding communities. This study aims to analyze the impact of oil contamination and to formulate strategies for managing and monitoring groundwater quality in the oil-contaminated soil recovery area at PKM 15,800 Lukut, Siak Regency, Riau Province. The research was conducted from May to December 2025 using a mixed-methods approach that combines environmental monitoring, laboratory analysis of groundwater samples, field observations, and socio-economic surveys of local communities. Groundwater samples were analyzed for Total Petroleum Hydrocarbon (TPH) parameters, including short-chain (C6–C9) and long-chain (C10–C36) hydrocarbons. The results show that although traces of TPH were detected during early monitoring, subsequent monitoring indicates that groundwater quality has remained below the established environmental quality standards. Ecologically, the affected area shows signs of ecosystem recovery through the presence of pioneer vegetation and diverse fauna, while socio-economic impacts include reduced oil palm productivity and community concerns regarding environmental safety. The study concludes that groundwater quality in the study area is generally stable after remediation, and that an integrated and proactive strategy—incorporating community participation, institutional support, and continuous environmental monitoring—is essential for sustainable groundwater management and long-term environmental recovery.